Հայ տպագրության զարգացման զուգահեռները - Ղարիբյան, Արմինե; Մկրտչյան, Արմինե (Հայաստանի ազգային գրադարան)
The book has always been valued as the most important value for the transmission of information. Along with the historical development of the society, it performed the complex function of transferring the achievements of the given period to the future generations, which made it possible to correctly assess the past. This phenomenon is more emphasized when we refer to the history of Armenian book art. Perhaps, for no people in the world, books and printing have had the same role and significance as in the life of the Armenian people.
Keywords: Հաղորդումներ; Գրատպության պատմություն